Gambaran Proses Penyembuhan Luka Perineum Ibu Nifas Hari ke 1 sampai 14 di BPS Umi Nadifah Pelintahan Kec.Pandaan Pasuruan - Basuki, Duwi; Farida, Luluk (Jurnal Keperawatan Bina Sehat, 2012)
Phenomenon which often happened in this time is to the number of incoming child bed mother pay a visit to service of health with sigh release blood smelling, fever body, and pain in bone at stitching hurt representing infection marking, most child bed mother say that them less know about how taking care of hurt of perineum truly. Target of research know picture process healing of hurt of perineum at day child bed mother 1 - 14 in BPS Umi Nadifah Leech District Of Pandaan Sub-Province of Pasuruan. descriptive Type Research, its population is all day child bed mother 7 - 14 in BPS Umi Nadifah Leech District Of Pandaan Sub-Province of Pasuruan with amount of sampel 16 responder. At this research of researcher use sampling technique of consecutive sampling. Variable in this research is picture process healing of hurt of perineum at day child bed mother to 7 - 14. Instrument which is used in this research is observation. Data analysed to use prosentase.Berdasarkan result of research in BPS Umi Nadifah Leech District Of Pandaan Sub-Province of Pasuruan can be concluded that almost semi Healing of Hurt of Perineum quickly counted 8 responder (50%).Diharapkan mother more is improving of knowledge about treatment of hurt of perineum either through mass media and also electronic media so that mother earn mempraktikkan of is way of taking care of perineum to assist process healing of hurt.Keyword: Hurt of Perineum, healing process, post partm